SKOR POLA PANGAN HARAPAN DAN HUBUNGANNYA DENGAN STATUS GIZI ANAK USIA 0,5 – 12 TAHUN DI INDONESIA - Yekti Widodo; Sandjaja Sandjaja; Fitrah Ernawati (Persagi, 2017)
ABSTRACTThe prevalence of undernutrition in Indonesia is still high compared to its neighbouring countries. The causes are quantity and quality of dietary intakes that can be assesed by dietary recall and desirable dietary pattern (DDP) respectively. The objective was to measure DDP and its association with nutritional status of 0,5-12-year-old Indonesian children. Data was obtained from SEANUTS Indonesia's research covering 3.600 children in 48 districts. Trained nutritionists collected food intakes and dietary pattern by 1x24 hour dietary recall. Nutrient intakes and DDP were calculated by food composition tables and 9 food groups respectively. DDP score were categorized into lowest (score <55), low (55-70), medium (71-84), and high (>85). Weight, length/height were measured by digital weight scale and length measuring board/microtoise. World Health Organization (WHO) child standard was used to calculate W/A, H/A, W/H Z-scores. Analysis was done to measure DDP and its association with nutritional status. The result showed that DDP child 0,5-1,9 years was 48,7 point, DDP child 2,0-5,9 years was 54,7 point, DD child 6,0-12,9 years was 48,8 point. The overall DDP was 49,9 point, far below the maximum value 100 point. DDP was higher among older age, urban areas, higher father education, and higher socioeconomic status. The risk of stunted was higher in low DDP (OR = 1,24; 95% CI 1,15-1,732) and underweight (OR = 1,27; 95% CI 1,16-1,38) but no risk for wasted. The conclusion DDP of Indonesian children was still low and it was associated significantly with stunting and underweight. ABSTRAK Prevalensi kekurangan gizi di Indonesia masih tinggi dibandingkan negara tetangga, penyebab adalah kuantitas dan kualitas asupan makanan, yang dapat dinilai dari konsumsinya dalam bentuk kualitas dan keragamannya. Penelitian bertujuan mengukur skor pola pangan harapan (PPH) dan hubungannya dengan status gizi anak usia 0,5-1,6 tahun, 2,0-5,9 tahun, dan 6,0-12,9 tahun di Indonesia. Data diperoleh dari penelitian SEANUTS Indonesia yang mencakup 3.600 anak di 48 kabupaten. Data asupan makanan dikumpulkan dengan cara recall 1x24 jam oleh ahli gizi yang terlatih. Asupan zat gizi dihitung menurut tabel komposisi bahan makanan dan skor PPH berdasarkan sembilan kelompok bahan makanan. Skor PPH dikategorikan sangat rendah (< 55), rendah (55-70), cukup (71-84), dan tinggi (>85). Berat badan diukur dengan timbangan digital dan panjang atau tinggi badan diukur dengan papan panjang badan atau microtoise. Status gizi anak dinilai berdasarkan Z-score indeks BB/U, TB/U BB/TB standar WHO. Hasil penelitian menunjukkan bahwa skor PPH konsumsi anak umur 0,5-1,9 tahun adalah 48,7, umur 2,0-5,9 tahun 54,7, dan umur 6,0-12,9 tahun 48,8. Secara keseluruhan skor PPH anak umur 0,5-12,9 tahun hanya 49,9 masih jauh di bawah skor ideal (100). Skor PPH cenderung lebih tinggi pada anak yang tinggal di perkotaan, tingkat pendidikan ibu lebih tinggi, dan status sosial ekonomi lebih tinggi. Anak dengan skor PPH rendah mempunyai risiko mengalami stunting dengan OR = 1,24; 95% CI 1,15-1,32 dan mengalami underweight dengan OR = 1,27; 95% CI 1,16-1,38, tetapi tidak menunjukkan berisiko wasting. Dimpulankan bahwa skor PPH anak Indonesia masih rendah dan berhubungan nyata dengan risiko stunting dan underweight.